2008
DOI: 10.1007/s00424-008-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine modulates excitatory synaptic transmission and suppresses neuronal death induced by ischaemia in rat spinal motoneurones

Abstract: Although adenosine is an important neuromodulator, its role in modulating motor functions at the level of the spinal cord is poorly understood. In the present study, we investigated the effects of adenosine on excitatory synaptic transmission and neuronal death induced by experimental ischaemia by using whole-cell patch-clamp recordings from lamina IX neurones in spinal cord slices. Adenosine significantly decreased the frequency of miniature excitatory postsynaptic currents (mEPSCs) in almost all neurones exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
(55 reference statements)
1
9
1
Order By: Relevance
“…), leading to presynaptic inhibition of excitatory transmission and eliciting an outward current in spinal VH neurons (Miyazaki et al . ). However, it is unclear why H 2 O 2 treatment in the presence of 2‐APB had no effect on R in even though an outward current and decrease of mEPSCs frequency were observed.…”
Section: Discussionmentioning
confidence: 97%
“…), leading to presynaptic inhibition of excitatory transmission and eliciting an outward current in spinal VH neurons (Miyazaki et al . ). However, it is unclear why H 2 O 2 treatment in the presence of 2‐APB had no effect on R in even though an outward current and decrease of mEPSCs frequency were observed.…”
Section: Discussionmentioning
confidence: 97%
“…How adenosine-induced A 2a R activation is toxic to spinal motor neurons remains unclear. As A 2a R activation is excitatory to spinal motor neurons (Miyazaki et al, 2008) and excitotoxicity is considered one of the primary mechanisms for spinal motor neuron degeneration (Cleveland and Rothstein, 2001), it is likely that elevated adenosine extensively stimulates pathologically increased A 2a R and subsequently contributes to motor neuron excitotoxicity. In addition, pharmacological inhibition of A 2a R-mediated transactivation of TrkB protects primary motor neurons from excitotoxic insults in cultures (Mojsilovic-Petrovic et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The A 2A receptor agonist, CGS21680, increases miniature excitatory postsynaptic currents in SC in the lamina IX neurones of spinal motoneurons, indicating that A 2A receptors modulate excitatory synaptic transmission [40]. We have demonstrated that A 2A antagonists reduce glutamate outflow in the first hours after brain ischemia [20].…”
Section: Discussionmentioning
confidence: 99%